Perbandingan Tingkat Kebisingan Berbagai Bahan Peredam pada Knalpot Sepeda Motor Racing - Ryanta Bhaskara, Surya; Sena, Boni (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The use of racing exhausts on motorised vehicles can cause uncomfortable and dangerous noise pollution if it exceeds the threshold set by the Minister of Environment. Based on the Decree of the Minister of Environment No 07/2009, the noise limit for motorbikes with engine capacity below 80 cc is 77 dB, 80-175 cc is 80 dB, and above 175 cc is 83 dB. This study aims to observe the comparison of noise levels of various silencer materials on racing motorbike exhausts in order to find the most effective material in reducing noise in accordance with these regulations. The noise measurement method follows the ISO 5130 standard, carried out when the engine is running idle and at engine speed range from 0 to 8000 RPM with a variety of different damping materials. The results show that at idle conditions, yellow Glasswool is the best damping material with the lowest noise level of 90.31 dBA, while Stainless wool shows the worst performance with an average noise level of 100.81 dBA. In contrast, in the 0-8000 RPM rotation condition, Stainless wool became the most superior silencer material with a noise level of 105.4 dBA, while grandma's hair Glasswool (fibreglass) became the worst with the highest noise level of 106.4 dBA. The conclusion of this study is that the optimal choice of silencer material can differ depending on the operating conditions of the racing exhaust, with yellow Glasswool being more effective at idle conditions and Stainless wool being more effective at maximum revs.